INVALSI data to investigate the characteristics of students, school, and society IV seminar "INVALSI data: a research and educational teaching tool" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
Data are precious resources and as such an asset of the community. Collected, ordered, studied data become a tool that allows us to open debates and make most useful decisions. The INVALSI Statistical Service followed up, on this premise, with the organization of the IV Seminar "INVALSI data: a tool for teaching and scientific research". The Institute's databases, in fact, allow researchers and teachers to investigate in depth the theme of education in schools from different points of view and the event allows them to participate in a lively confrontation on the subject. The authors of the contributions collected in this volume investigate in depth the characteristics of students, schools and society. As a Statistical Service we hope that the reading of the volume confirms what has been written on the importance of data and their use, which will allow an ever-growing audience to enrich their knowledge on the subject of education and be a means of giving life to always new ideas for further reflection.